2021
DOI: 10.1017/ice.2021.2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of severe acute respiratory coronavirus virus 2 (SARS-CoV-2) in outpatients: A multicenter comparison of self-collected saline gargle, oral swab, and combined oral–anterior nasal swab to a provider collected nasopharyngeal swab

Abstract: Background: Widespread testing for severe acute respiratory coronavirus virus 2 (SARS-CoV-2) is necessary to curb the spread of coronavirus disease 2019 (COVID-19), but testing is undermined when the only option is a nasopharyngeal swab. Self-collected swab techniques can overcome many of the disadvantages of a nasopharyngeal swab, but they require evaluation. Methods: Three self-collected non-nasopharyngeal swab techniques (saline gargle, oral swab and combined oral-anterior nasal swab)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 14 publications
3
54
1
Order By: Relevance
“…This study met the criteria of a quality improvement project in accordance with institutional guidelines. One swab was stored in McMaster Molecular Medium (MMM) (Bay Area Health Trustee Corp, Canada), a guanidine thiocyanate-based viral inactivation medium for rRT-PCR testing [12] , and the second was kept dry in a sterile 50 mL conical tube (Corning Inc., USA) for ID NOW™ testing. Individuals collecting specimens were advised to store the dry swabs for 1 hour at room temperature or 2-8 °C for up to 24 hours if delays in transport were anticipated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study met the criteria of a quality improvement project in accordance with institutional guidelines. One swab was stored in McMaster Molecular Medium (MMM) (Bay Area Health Trustee Corp, Canada), a guanidine thiocyanate-based viral inactivation medium for rRT-PCR testing [12] , and the second was kept dry in a sterile 50 mL conical tube (Corning Inc., USA) for ID NOW™ testing. Individuals collecting specimens were advised to store the dry swabs for 1 hour at room temperature or 2-8 °C for up to 24 hours if delays in transport were anticipated.…”
Section: Methodsmentioning
confidence: 99%
“…All SARS-CoV-2 testing was performed at the Shared Hospital Laboratory (Toronto, Canada). Real-time RT-PCR testing to detect the E gene and UTR of SARS-CoV-2 was performed as previously described [ 11 , 12 ] . Testing with the ID NOW™ COVID-19 assay was performed as per manufacturer's recommendations (Abbott Diagnostics Inc, USA), with dry swabs being inoculated into the elution buffer within the Sample Receiver cartridge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, gargle specimens have also been estimated sensitive for SARS-CoV-2 infection diagnosis compared to NPS including 50 inpatients (26) and outpatients (10,27) with confirmed COVID-19. Ct values of gargle specimens were higher than in NPS in these three studies including one with 19 620 outpatients which is in line with findings in our study (10,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, gargle specimens have also been estimated sensitive for SARS-CoV-2 infection diagnosis compared to NPS including 50 inpatients (26) and outpatients (10,27) with confirmed COVID-19. Ct values of gargle specimens were higher than in NPS in these three studies including one with 19 620 outpatients which is in line with findings in our study (10,26,27). Interestingly Goldfard et al, when analyzing 40 COVID-19 outpatients concluded that gargle specimens had higher sensitivity compared to saliva specimens (97.5 % CI 86.8-99.9 % compared to 78.8 CI 95 % 61.0-91.0 %) which is inconsistent with our results, although saliva collection methods were similar (10).…”
Section: Discussionmentioning
confidence: 99%